2017
DOI: 10.1002/smll.201603610
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Surficial Bifunctional Nanolayer on Nb2O5 for Ultrastable Electrodes for Lithium‐Ion Battery

Abstract: Safe and long cycle life electrode materials for lithium-ion batteries are significantly important to meet the increasing demands of rechargeable batteries. Niobium pentoxide (Nb O ) is one of the highly promising candidates for stable electrodes due to its safety and minimal volume expansion. Nevertheless, pulverization and low conductivity of Nb O have remained as inherent challenges for its practical use as viable electrodes. A highly facile method is proposed to improve the overall cycle retention of Nb O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 58 publications
2
32
0
Order By: Relevance
“…X‐ray photoelectron spectroscopy (XPS) was performed to analyze the components and valence states of the samples. As shown in Figure c, two peaks around 206.9 and 209.7 eV are ascribed to Nb3d 3/2 and Nb3d 5/2 , respectively, which are in accordance with Nb 5+ in T‐Nb 2 O 5 …”
supporting
confidence: 83%
“…X‐ray photoelectron spectroscopy (XPS) was performed to analyze the components and valence states of the samples. As shown in Figure c, two peaks around 206.9 and 209.7 eV are ascribed to Nb3d 3/2 and Nb3d 5/2 , respectively, which are in accordance with Nb 5+ in T‐Nb 2 O 5 …”
supporting
confidence: 83%
“…It exhibits high reversible capacities of 179.7 and 103.6 mA h g −1 at the current densities of 0.5 and 5 A g −1 , respectively. Ag nanoparticle coated nitridated Nb 2 O 5 electrode also shows high rate performances …”
Section: Nb2o5 Electrodesmentioning
confidence: 95%
“…Thus, exploring the practical energy storage applications of micrometer dimensional Nb 2 O 5 electrodes would be an interesting and significant topic. Typically, Kim et al have prepared some micrometer‐sized Nb 2 O 5 ‐based electrodes including pure Nb 2 O 5 , nitridated Nb 2 O 5 (N‐Nb 2 O 5 ), and Ag nanoparticles coated nitridated Nb 2 O 5 microparticles (Ag‐N‐Nb 2 O 5 ), then investigated their electrochemical performances ( Figure ) . It was found that Ag‐N‐Nb 2 O 5 exhibited high rate capacity (155, 108, 87 mA h g −1 at the current densities of 1, 3, 5 A g −1 , respectively) and excellent long‐cycle character (69 mA h g −1 after 3000 cycles at 3 A g −1 ) (Figure c,d).…”
Section: Nb2o5 Electrodesmentioning
confidence: 99%
See 2 more Smart Citations